2013
DOI: 10.1007/s13277-012-0609-7
|View full text |Cite
|
Sign up to set email alerts
|

miR-133b acts as a tumor suppressor and negatively regulates FGFR1 in gastric cancer

Abstract: MicroRNAs (miRNAs) are a class of small noncoding RNAs that negatively regulate protein expression by binding protein-coding mRNAs and repressing translation. Accumulating evidence suggests that miRNAs are involved in cancer development and progression, acting as either tumor suppressors or oncogenes. Intriguingly, it has been shown that miR-133b was significantly downregulated in several types of cancers. However, its role and relevance in gastric cancer are still largely unknown. We showed that miR-133b was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 32 publications
4
41
1
Order By: Relevance
“…We also found that cells transfected with miR-133b mimics inhibited the cell proliferation, which strongly suggests that miR-133b acts as tumor suppressor in CRC. At the same time, similar results had also been observed in osteosarcoma (Novello et al, 2013), gastrointestinal stromal tumor (Yamamoto et al, 2013), gastric cancer (Wen et al, 2013) as well as bladder cancer (Yamasaki et al, 2012). However, the targets of miR-133b that regulates in CRC have not been established previously.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We also found that cells transfected with miR-133b mimics inhibited the cell proliferation, which strongly suggests that miR-133b acts as tumor suppressor in CRC. At the same time, similar results had also been observed in osteosarcoma (Novello et al, 2013), gastrointestinal stromal tumor (Yamamoto et al, 2013), gastric cancer (Wen et al, 2013) as well as bladder cancer (Yamasaki et al, 2012). However, the targets of miR-133b that regulates in CRC have not been established previously.…”
Section: Discussionsupporting
confidence: 67%
“…However, current studies indicate a broader expression pattern of miR-133b in diverse tissues. Moreover, most of the studies showed that miR-133b was down-regulated in some human malignancies, such as osteosarcoma (Novello et al, 2013), gastrointestinal stromal tumor (Yamamoto et al, 2013), gastric cancer (Wen et al, 2013) as well as bladder cancer (Yamasaki et al, 2012). Therefore, up-regulating miR-133b or exogenously providing its analogous pharmaceutical compounds might provide effective cancer therapies for tumors.…”
Section: Mir-133b Acts As a Tumor Suppressor And Negatively Regulatesmentioning
confidence: 99%
“…It is well known that each miRNA may regulate multiple gene targets. Previous studies have identified numerous target genes of miR-133b in a variety of tumor types; these genes include TBPL1, fibroblast growth factor receptor-1, specificity protein-1 and epidermal growth factor receptor (11,12,(18)(19)(20); thus suggesting that the roles of miR-133b in tumorigenesis may be cell-or tissue-specific. The present study demonstrated that miR-133b overexpression inhibited, whereas its suppression increased, endogenous S1PR1 protein expression in NPC cells.…”
Section: A B C D Discussionmentioning
confidence: 99%
“…miR-133b has been identified as a tumor suppressor in numerous types of human cancer (9); miR-133b is often downregulated in gastric cancer and its overexpression has been shown to reduce the metastatic potential of gastric cancer cells (10,11). In addition, miR-133b has been shown to be downregulated in colorectal cancer tissues, as compared with adjacent tissues (12), and has been found to inhibit the proliferation of colon cells by suppressing the TATA box-binding protein-like protein 1 (TBPL1) (12).…”
Section: Introductionmentioning
confidence: 99%
“…miR‐133b was first considered to be a muscle‐specific microRNA, however, some recent research revealed that there was significant correlation between abnormal expression of miR‐133b and tumorigenesis. miR‐133b may affect the ability of tumor cell proliferation, apoptosis, and invasion by regulating the expression of different target genes 8, 9. The abnormal expression of miRNA may act as a potential prognostic factor.…”
Section: Introductionmentioning
confidence: 99%